Pedogenesis, Permafrost, and Ecosystem Functioning: Feedbacks and Interactions along Climate Gradients across the Tibetan Plateau - Baumann, Frank (Universität Tübingen, 2014)
This thesis was conducted within the scope of a graduation fellowship from the state of Baden-Württemberg, Germany (Grant No.: VI 4.2-7631.2/Baumann) in cooperation with the Depart-ment of Ecology, Peking University, Beijing. Scientists specialised in both ecology and soil science investigated the same sites, thus allowing an interdisciplinary approach to evaluate soil properties, C and N cycles as well as geomorphological processes in close connection to ecosys-tem interrelations on the Tibetan Plateau. The research sites are located along a 1,200 km long north-south transect at altitudes between 2,925 and 5,105 m ASL. Two thirds of the Tibetan Plateau is influenced by permafrost. Due to the high sensitivity to global climate warming and land use changes, permafrost degradation processes are widespread, increasing the heterogeneity of soil formation, soil hydrology, and related soil chemical processes (i.e. C and N cycling). In order to account for the resulting extremely diverse ecosystem, investigations at different spatial scales related to large-scale climate patterns were performed. The scales comprise the total main transect, the split transect into an eastern and western section, diverse catenas along distinct geomorphological relief units, and finally the single site soil profiles. The first part of this work examines C and N contents as well as portions of plant available min-eralised nitrogen in relation to their main influencing parameters. For investigations on land-scape scale, soil moisture was found to have the strongest effect on C and N cycling, followed by CaCO3-content and soil texture. Altogether, the general linear model explains 64% and 60% of the variation of soil organic carbon (SOC) and total nitrogen (NT) contents, respectively. Thereby, two aspects are important: (1) temperature variables have no significant influence and (2) indicators for soil development (i.e. CaCO3 and soil texture) are included besides commonly con-sidered ecological (i.e. moisture, temperature and biomass) ...